FOXN1 recombinant protein enhances T‐cell regeneration after hematopoietic stem cell transplantation in mice. Issue 6 (12th May 2016) - Song, Yinhong; Su, Min; Zhu, Jing; Di, Wen; Liu, Yalan; Hu, Rong; Rood, Debra; Lai, Laijun
Abstract : Administration of rFOXN1 protein that contains cell‐penetrating peptides into hematopoietic stem cell transplantation (HSCT) mice increases the number of thymic epithelial cells, which results in enhanced thymopoiesis and increased number of functional peripheral T cells. rFOXN1 has the potential to be used in enhancing T‐cell regeneration in patients following HSCT. Abstract : A prolonged period of T‐cell recovery is the major challenge in hematopoietic stem cell transplantation (HSCT). Thymic epithelial cells (TECs) are the major component of the thymic microenvironment for T‐cell generation. However, TECs undergo degeneration over time. FOXN1 plays a critical role in TEC development and is required to maintain adult TECs for thymopoiesis. To investigate the potential application of FOXN1, we have cloned and expressed recombinant FOXN1 protein (rFOXN1) that was fused with cell‐penetrating peptides. We show here that the rFOXN1 protein can translocate from the cell surface into the cytoplasm and nucleus. Administration of rFOXN1 into both congenic and allogeneic HSCT recipient mice increased the number of TECs, resulting in enhanced thymopoiesis that led to an increased number of functional T cells in the periphery. The increased number of TECs is due to the enhanced survival and proliferation of TECs. Our results suggest that rFOXN1 has the potential to be used in enhancing T‐cell regeneration in patients following HSCT.